Kajian Kriminologis Terhadap Pencurian Barang Inventaris Universitas Nusa Cendana Yang Dilakukan Secara Berlanjut Dan Bersama-Sama - Lere, Juandry Pangeran Alcicho; Heryanto Amalo,; Debi F. Ng. Fallo, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Theft is a criminal offense that frequently occurs and continues to develop within society, including in academic environments. The case of theft of inventory assets at Nusa Cendana University, carried out continuously, indicates the presence of underlying criminological factors. This study aims to analyze the causal factors and the efforts to address such criminal acts. This research employs an empirical method with a qualitative approach. Data were obtained through interviews and literature review, and were analyzed using descriptive qualitative methods. The results of the study indicate that the factors causing theft consist of internal factors, namely intention and consumptive behavior, and external factors, namely opportunity and peer influence. Efforts to address the crime are carried out through repressive measures in the form of law enforcement and rehabilitative measures in the form of offender development. Thus, the occurrence of theft is influenced by the interaction between internal and external factors, so that countermeasures must be carried out comprehensively through both legal enforcement and rehabilitative approaches. It is recommended that young people engage in positive social interactions and enhance legal awareness, supported by social concern and community control, while Nusa Cendana University should strengthen its security system to prevent theft and protect campus assets. On the other hand, law enforcement officers must carry out firm, professional, and consistent law enforcement, while also improving rehabilitative efforts through structured correctional programs so that offenders develop legal awareness and do not reoffend.